PUBLIC RELATIONS AND EMPLOYEE PERFORMANCE IN NIGERIAN INSTITUTIONS OF HIGHER LEARNING - Nguru, Muhammad Nura; Ibrahim, Adamkolo Mohammed (Universitas Negeri Yogyakarta, 2018)
Organizations’ internal publics, which generally comprises two categories of personnel, namely management staff and employees constitute some of the key elements that contribute toward realizing the goals and objectives of the organization. However, unlike non-academic organizations, institutions of higher (academic) learning have two additional categories of internal publics — academic staff and students. This makes such institutions a bit unique. Public relations (PR) as a management function and tool is utilized by the management between itself and all categories of internal publics to facilitate smooth information dissemination and communication for enhanced job performance. Hence, a unique type of PR practice capable of addressing the characteristic needs of the academic staff (who are directly involved with the students) in addition to those of the non-academic staff will be required. A critically review of extant literature surrounding the impacts of the practice of PR on job performance among employees of Nigerian institutions of higher learning was performed. Additionally, critical intra-organizational PR media capable of addressing the characteristic and specific needs of the overall and specific internal publics were underscored and some policy recommendations offered. This article concludes that effective PR (a PR practice that addresses both the comprehensive and specific needs of the various classifications of internal publics) enhances job performance and productivity.HUBUNGAN MASYARAKAT DAN KINERJA KARYAWAN DI LEMBAGA PENDIDIKAN TINGGI NIGERIAInternal publik dalam sebuah organisasi yang pada umumnya terdiri dari dua bagian yaitu manajemen staf dan karyawan, merupakan beberapa elemen kunci yang memberikan kontribusi terhadap realisasi sasaran dan tujuan organisasi. Namun, tidak seperti organisasi non-akademik, institusi akademik memiliki dua bagian tambahan lain dalam internal publiknya – staf akademik dan siswa. Hal inilah yang kemudian membuat institusi-instistusi akademik memiliki sedikit keunikan. Public Relations (PR) sebagai fungsi manajemen digunakan oleh institusi untuk memfasilitasi penyampaian informasi dan komunikasi untuk meningkatkan performa kerja antara manajemen dan seluruh bagian publik internalnya. Oleh karena itu, PR yang memiliki keunikan seperti ini harus mampu menganalisa hal-hal apa saja yang menjadi kebutuhan staf akademik (yang secara langsung terlibat dengan siswa) dan juga staf non-akademik yang nantinya akan dibutuhkan. Sebuah tinjauan kritis menghasilkan temuan mengenai dampak praktik PR pada performa kerja para karyawan yang bekerja di institusi-institusi Nigeria. Selain itu, media intra-organisasi PR yang kritis harus mampu menganalisa karakteristik dan kebutuhan-kebutuhan tertentu dari seluruh ataupun sebagian kecil publik internal dan kebijakan-kebijakan yang ditawarkan. Penelitian ini menyimpulkan bahwa PR yang efektif (praktik PR yang menganalisa secara mendalam ataupun spesifik kebutuhan-kebutuhan berbagai kalangan yang merupakan bagian dari publik internal) dapat meningkatkan performa pekerjaan dan produktivitas.